The Main Character Personality of Alif Fikri in A. Fuadi's Novel Ranah 3 Warna: Literary Psychology Approach - Hasibuan, Laila Halwi (Institute of Computer Science (IOCS), 2020)
Literary work is a picture of the totality of people's lives that created it. After that the creators of literary works (writers) can use their experiences, thoughts, and imaginary processes so that the work is interesting to read, understand, enjoy, and analyze to capture and understand the messages it receives. Writing this thesis is done with the aim of obtaining a description of the personality of the main character in A. Fuadi's Ranah 3 Warna novel. With this aim, the author examines the novel Ranah 3 Warna by A. Fuadi by applying a literary psychology approach. This research discusses the personality of the main character Alif. Fikri in the novel Ranah 3 Warna by A. Fuadi uses the psychoanalytic theory of Sigmunt Freud. From the results of this study, there are 21 personalities of the main character Alif, namely: never give up.